PENGEMBANGAN SENDRATARI KAMMAVIBHANGA SEBAGAI MEDIA PEMBELAJARAN MORAL SISWA SEKOLAH MINGGU BUDDHIS - Adisti, Kanthi; Endah Ekowati, Wilis Rengganiasih; Suranto, Suranto (Jurnal Pencerahan, 2020)
The purpose of this study is to explain the transformation process of Kammavibhanga reliefs into the form of ballet, the process of making Kammavibhanga Ballet, and that Kammavibhanga Ballet is suitable as a medium of moral learning for SMB students. This study is about the moral learning of Buddhist Sunday School (SMB) students through Kammavibhanga Ballet. The background is that the moral attitude of SMB students is still not good. The research method used is Research and Development level 4 using the ADDIE development method or Analyze, Design, Development, Implementation, and evaluation. The tested subjects were Vidha Panna High School, Dhamma Ratana Monastery, and Vijjadhara High School consisting of teachers and students from 6th grade to junior high school. The product was tested by showing a video of Kammavibhanga Ballet and then giving a user questionnaire to students, and a product feasibility questionnaire for SMB teachers. The data collection was done by observation to find problems in the field, interviews to find out the understanding of Kammavibhanga Relief from the speakers, namely SMB teachers and questionnaires to carry out product validation and user's trials. The data in this study were analyzed using needs analysis techniques, and data analysis techniques of expert judgment and trial subjects. Based on the findings, it can be concluded that (1) from the Kammavibhanga relief transformation process, the relief used is the 25th relief about giving funds to ascetics which were divided into two scenes, (2) the Kammavibhanga ballet making process is carried out for two and a half months beginning with the scenario making accompaniment, creation of the dance movements, rehearsals, and recordings, (3) the feasibility of Kammavibhanga Ballet based on the results of trials to students and SMB teachers, and the results of expert validation, the ballet is feasible to be produced and used as a medium of moral learning for SMB students. Keywords: Ballet Development, Kammavibhanga, Learning Media, Buddhist Sunday School.